Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
if you noted 2-6+4=0 ⇒z₁=1 ⇒ one of factor is (z-1)
so 2z²-2z-4z+4=0
(2z²-2z)-(4z-4)=0
2z(z-1)-4(z-1)=0
(z-1)(2z-4)=0
2z-4=0
2z=4
z₂=2
Answer: z₁=1, z₂=2
so 2z²-2z-4z+4=0
(2z²-2z)-(4z-4)=0
2z(z-1)-4(z-1)=0
(z-1)(2z-4)=0
2z-4=0
2z=4
z₂=2
Answer: z₁=1, z₂=2
2z²-6z+4=0
Divide by 2 to everything
z²-3z+2=0
Think of two numbers that multiply to get 2 and add to get -3 in order to factorise
These numbers are -2 and -1
(z-2)(z-1)=0
Therefore z= 2 and z= 1
Divide by 2 to everything
z²-3z+2=0
Think of two numbers that multiply to get 2 and add to get -3 in order to factorise
These numbers are -2 and -1
(z-2)(z-1)=0
Therefore z= 2 and z= 1
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.